Dihedral angle control to improve the charge transport properties of conjugated polymers in organic field effect transistors - Dharmapurikar, Satej S.; Chithiravel, Sundaresan; Mane, Manoj V.; Deshmukh, Gunvant; Krishnamoorthy, Kothandam (Chemical Physics Letters, 2018)
Diketopyrrolopyrrole (DPP) and i-Indigo (i-Ind) are two monomers that are widely explored as active materials in organic field effect transistor and solar cells. These two molecules showed impressive charge carrier mobility due to better packing that are facilitated by quadrupoles. We hypothesized that the copolymers of these monomers would also exhibit high charge carrier mobility. However, we envisioned that the dihedral angle at the connecting point between the monomers will play a crucial role in packing as well as charge transport. To understand the impact of dihedral angle on charge transport, we synthesized three copolymers, wherein the DPP was sandwiched between benzenes, thiophenes and furans. The copolymer of i-Indigo and furan comprising DPP showed a band gap of 1.4 eV with a very high dihedral angle of 179 degrees. The polymer was found to pack better and the coherence length was found to be 112 angstrom. The hole carrier mobility of these polymer was found to be highest among the synthesized polymer i. e. 0.01 cm(2)/vs. The copolymer comprising benzene did not transport hole and electrons. The dihedral angle at the connecting point between i and Indigo and benzene DPP was 143 angstrom, which the packing and consequently charge transport properties. (C) 2018 Elsevier B. V. All rights reserved.

Conversion of curved assemblies into two dimensional sheets - Deshmukh, Gunvant; Krishnamoorthy, Kothandam (Nanoscale, 2019)
The design and preparation of organic two dimensional (O2D) sheets and their conversion to curved nanostructures is in its infancy. To convert a flat structure into a curved structure, the molecule must have multiple interaction possibilities and an in-built twist. The conjugated small molecule iso-Indigo (i-Indigo) comprises two phenyl rings that are twisted (the dihedral angle is 15 degrees) at the junction. The i-Indigo has been connected with moieties that impart hydrogen bonding and van der Waals interactions. Due to the presence of the cloud in i-Indigo, - interactions are also present in the molecule. While all three interactions are in operation, rings and toroids are formed. Upon addition of hydrogen bonding competing solvents, the rings and toroids unravel to form O2D sheets. Control molecules that don't have hydrogen bonding moieties and - interactions form random assemblies. Please note that the rings, toroids and O2D sheets are formed in a single solvent by simple dissolution, unlike previous approaches that involve multiple steps and solvents.

Effect of aromatic rings and substituent on the performance of lithium batteries with rylene imide cathodes - Aher, Jagdish; Graefenstein, Alexander; Deshmukh, Gunvant; Subramani, Kumar; Krueger, Bastian; Haensch, Mareike; Schwenzel, Julian; Krishnamoorthy, Kothandam; Wittstock, Gunther (ChemElectroChem, 2020)
Rylene imides (RIs) are attractive organic battery materials because of the inherent modularity of the molecules. While strong aggregation of RIs is disadvantageous for fast lithium-ion transport in the organic active material, decreasing the solubility of the RIs in battery electrolytes is essential to avoid performance fading. Therefore, the design and synthesis of RIs for lithium batteries is a non-trivial task that must, among other considerations, balance lithium-ion transport in the solid material vs. low solubility by controlling aggregation and packing. We have chosen triphenylamine (TPA) as a substituent which disrupts the aggregation but maintains a low solubility due to increased aromaticity of TPA. We have synthesized three RIs with one, two, and four aromatic units in the core. All of them showed stable specific capacity over 300 charge-discharge cycles. The batteries also showed specific capacities close to their theoretical capacities with 97-99 % coulombic efficiency. The maximum specific energy and specific power were 197 mWh g(-1) and 37 mW g(-1), respectively.
Keywords: lithium-ion batteries; organic cathode material; rylene imides; solubility; triphenylamine